Metabolite mimicry identifies butyrate analogs with select protective functions in the intestinal mucosa - Alfredo Ornelas; Jacob A. Countess; Ji Yeon Kim; Rachel H. Cohen; Brittany D. Gomez; Rebecca L. Roer; Faiz Minhajuddin; Kiranmayee Yenugudhati Vijaya Sai; Liheng Zhou; Julia L. M. Dunn; Caleb Chandler; Philip Reigan; et al. (Proceedings of the National Academy of Sciences, 2026)
Microbial-derived short-chain fatty acids regulate a variety of pathways in the healthy colonic mucosa. In particular, butyrate serves as the primary energy source for colonocytes and regulates gene transcription by stabilizing the transcription factor hypoxia-inducible-factors (HIF) and functioning as a histone deacetylase (HDAC) inhibitor. A limitation of butyrate as a therapeutic is its rapid metabolism in differentiated colonocytes. Furthermore, intestinal stem cells (ISCs) respond differently to butyrate, preferentially using glucose for energy procurement. To address these limitations, we explored metabolite mimicry to identify compounds with potent or selective biological responses within the butyrate pathway(s). We found an analog, 3-chlorobutyrate (3-Cl BA), that significantly enhances epithelial barrier formation and wound healing in vitro. Mechanistically, we revealed that 3-Cl BA is a potent HDAC inhibitor. Furthermore, unlike butyrate, 3-Cl BA does not stabilize HIF and it is not used as metabolic fuel. In vivo studies in a dextran sulfate sodium-colitis model revealed that contrary to butyrate, 3-Cl BA is protective. Studies in stem-like colonoids demonstrated that only butyrate inhibits ISC proliferation and differentiation. Furthermore, it was recently reported that HIF stabilization inhibits ISCs activity. Given the fact that butyrate but not 3-Cl BA stabilizes HIF, we surmised that 3-Cl BA would circumvent these detrimental functional consequences. We demonstrate here that pharmacologic HIF stabilization inhibits colonoid differentiation and that genetic loss of HIF significantly promotes ISC differentiation. This study reveals a promising butyrate analog protective in colitis and demonstrates the advantages of metabolite mimicry to dissect selective biological functions from major metabolites in the gut.